Association of social support with cognition among older adults in China: A cross-sectional study - Li, Benchao; Guo, Yan; Deng, Yan; Zhao, Siqi; Li, Changfeng; Yang, Jiajia; Li, Qiuying; Yan, Yaqiong; Li, Fang; Li, Xiaonuan; Rong, Shuang (Frontiers in Public Health, 2022)
Objective: This study aimed to examine the relationship between social support and its sub-domains and cognitive performance, and the association with cognitive impairment among older adults in China. Design: A cross-sectional study. Setting and Participants: We included 865 community-based individuals aged 65 and above from Hubei province, China. Methods: The level of social support was evaluated using the social support rating scale (SSRC). The Mini-Mental State Examination was adopted to assess cognitive function, and its cut-offs were used to determine cognitive impairment among the participants. Multiple linear regression models and logistic regression models were used to estimate the  and odds ratios (ORs) and their 95% confidence intervals (CIs), respectively. Results: The participants were divided into quartiles 1-4 (Q1-Q4) according to the total scores of SSRC. After adjusting for sociodemographic characteristics, lifestyle factors, history of diseases, for MMSE scores, compared to these in Q1, the  of Q2-Q4 were -0.22 (-0.88, 0.43), 0.29 (-0.35, 0.94), and 0.86 (0.19, 1.53), respectively; For cognitive impairment, the ORs of Q2-Q4 were 1.21 (0.80, 1.82), 0.62 (0.40, 0.94), and 0.50 (0.32, 0.80), respectively. Considering SSRC scores as the continuous variable, with per 1-unit increase, the  was 0.05 (0.02, 0.09) for the cognitive score, and the OR was 0.95 (0.92, 0.98) for cognitive impairment. In addition, higher levels of both subjective support and support utilization were related to better MMSE performance and lower risks of cognitive impairment. Conclusion and Implications: Among the older adults in China, as expected, there is a positive relationship between social support and cognitive performance, and high levels of social support, particularly in support utilization, were related to low risks of cognitive impairment. More social support should be provided in this population to improve cognitive function and reduce the risks of cognitive impairment.